Identification of Potential Hazards and Operational Problems in Coloumn Combination V-0301 at PT Pertamina's Caustic Treater Unit Using the HAZOP Method - Syifa Zainur Anwar, Mochamad; Muzaki, Hafiz; Shakira Azhar, Bryan; Wahyu Nuryana, Yardan; Sulistiyo Nugroho, Budi (Advances In Social Humanities Research, 2024)
The presence of harmful gases such as H?S and mercaptans in the natural gas purification process requires safe handling to avoid the risk of equipment damage and danger to the environment and occupational safety. This study aims to analyze occupational safety risks in the V-0301 Combination Column at the Caustic Treater Unit (CTU) of CPP Gundih, PT Pertamina EP Cepu Asset 4 Zone 11 using the Hazard and Operability Study (HAZOP) method. Observed processes include pre-wash, extraction, and water wash, with NaOH as the primary solvent and demineralized water to remove impurities from natural gas. The analysis is carried out by identifying potential hazards and process deviations based on operating parameters such as pressure, temperature, and flow. The results point to several key risk scenarios, such as the potential for corrosion due to excessive NaOH concentrations and failure of pressure control systems. Risk mitigation recommendations include improved control systems, periodic inspections, and safety training for operators. The study contributed to the improvement of occupational safety and operational reliability of CTU units in natural gas processing facilities